2019
DOI: 10.1200/jco.2019.37.4_suppl.677
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of the effect of FTD/TPI in patients treated in RECOURSE by prognostic factors.

Abstract: 677 Background: The Phase III RECOURSE trial, in patients (pts) with metastatic colorectal cancer (mCRC) refractory to standard therapies, demonstrated that trifluridine/tipiracil (FTD/TPI) significantly extended overall survival (OS) and progression-free survival (PFS) versus placebo in all subgroups, regardless of age, geographical origin, or KRAS status, with acceptable safety. Literature reports have shown optimal benefit for pts with low tumor burden (< 3 metastatic sites), indolent disease (≥ 18 mo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…23 The Italian real world data (RWD) study showed a PS 0, a normal lactate dehydrogenase, and time from diagnosis > 18 months, which were independently associated with a greater likelihood of being progression-free at 6 months 20 ( Table 2). A recent analysis of the RECOURSE 28 compared patients with good prognostic characteristics (GPCs), defined as low tumor burden (< 3 metastatic sites), indolent disease (! 18 months since diagnosis of first metastasis), Eastern Cooperative Oncology Group PS 0 to 1, and no liver metastasis and patients with poor prognostic characteristics (PPCs), defined as high tumor burden and/or aggressive disease.…”
Section: Trifluridine/tipiracilmentioning
confidence: 99%
“…23 The Italian real world data (RWD) study showed a PS 0, a normal lactate dehydrogenase, and time from diagnosis > 18 months, which were independently associated with a greater likelihood of being progression-free at 6 months 20 ( Table 2). A recent analysis of the RECOURSE 28 compared patients with good prognostic characteristics (GPCs), defined as low tumor burden (< 3 metastatic sites), indolent disease (! 18 months since diagnosis of first metastasis), Eastern Cooperative Oncology Group PS 0 to 1, and no liver metastasis and patients with poor prognostic characteristics (PPCs), defined as high tumor burden and/or aggressive disease.…”
Section: Trifluridine/tipiracilmentioning
confidence: 99%
“…Выделенные на основании данного анализа прогностические группы хорошего (индолентное течение болезни и небольшая распространенность) и неблагоприятного прогноза показали значимые различия в выживаемости без прогрессирования и общей выживаемости независимо от возраста пациента, статуса по шкале ECOG, мутационных характеристик опухоли и наличия метастазов в печени. Отсутствие метастазов в печени явилось наиболее значимым благоприятным фактором в процессе терапии FTD / TPI: медианы общей выживаемости составили 16,4 мес против 7,6 мес соответственно [103]. В исследовании A. Tanaka и соавт.…”
Section: -4' 2020unclassified
“…DBT and ACT can help them to improve their tolerance of negative feelings, reduce behavioral impulses, and enhance their ability to cope effectively with illness [5]. As an important method of psychological treatment for psychological disorders, positive thinking therapy has also played a key role in promoting patients' physical and mental health in clinical practice [6]. Domestic and international studies have shown that the interventions of positive thinking therapy in hypertension, diabetes, chronic pain, cancer, chronic inflammation, and perioperative patients can effectively relieve patients' physical pain, improve patients' emotional disorders, reduce psychological stress, and improve the quality of daily life, which have shown good results in clinical application [7].…”
Section: Introductionmentioning
confidence: 99%